1995
DOI: 10.1093/ajcn/62.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sodium restriction in the prophylaxis of hypertensive disorders of pregnancy: effects on the intake of other nutrients

Abstract: Dietary sodium restriction is used in the Neth erlands in the prophylaxis of preeclampsia. To study the effects of long-term sodium restriction on the intake of other nutrients and the outcome of pregnancy, 6 8 healthy nulliparous pregnant women were randomly assigned to either a low-sodium diet (20 mmol/24 h) or an unrestricted diet. The diet was consumed between week 14 of gestation and delivery. The dietary intakes of energy, fat, protein, carbohydrate, sodium, potassium, and calcium were esti mated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Hence, we wanted to characterize the outcome of rat offspring born from dams on low-sodium diet. However, many studies have shown that dietary sodium restriction in humans does not reduce gestational hypertension (14,47). Our findings in the rat would support the latter statement.…”
supporting
confidence: 82%
“…Hence, we wanted to characterize the outcome of rat offspring born from dams on low-sodium diet. However, many studies have shown that dietary sodium restriction in humans does not reduce gestational hypertension (14,47). Our findings in the rat would support the latter statement.…”
supporting
confidence: 82%
“…However, there is inadequate evidence to support zinc supplementation to improve maternal serum levels as a therapeutic target for preeclampsia prevention. The potential implications of single mineral supplementation or dietary manipulation without adequate consideration of the impact on other nutrients must be considered , …”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen gamma is also an acute phase protein which is known to increase by 100% during pregnancy and is expressed by the liver [16]. Fibrinogen is a precursor of fibrin, which is one of the main components of blood clots generated during the hemostatic response.…”
Section: Discussionmentioning
confidence: 99%